ANALISIS INOVASI PERSONAL BRANDING KOMENG PASCA TERPILIH SEBAGAI ANGGOTA DPD RI (STUDI PADA MEDIA SOSIAL) - Sari, Dwi Rizky Yuliana; Budianto, Kun; Afriany, Deany (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2026)
This study analyzes the personal branding innovation of ALFIANSYAH BUSTAMI (Komeng) after officially serving as a member of the Regional Representative Council of the Republic of Indonesia (DPD RI) Commission II. Using a descriptive qualitative method, this study processed data from documentation of Komeng activities after being elected, social media content analysis, and public responses in the form of netizen comments. The analysis was conducted using the framework of Hubert Komeng Rampersad's 8 Criteria for Authentic Personal branding, to understand how personal branding innovation was formed and influenced public perception. The results show that Komeng succeeded in building a new model of personal branding for state officials that not only shows simplicity and humor, but also emphasizes the substance of work. Komeng utilizes his background as a comedian as a form of specialization to simplify technical issues of Commission II such as agriculture, forestry, infrastructure, transportation, and public services into relevant, easy-to-understand, and close-to-the-public language. Through an authentic, humorous, yet meaningful communication style, Komengdemonstrates authenticity and consistency that have not changed since before entering politics. This study shows that Komeng post-inaugural activities, whether through working visits, plenary sessions, cross-institutional collaboration, or social engagement, increased his visibility and perseverance as a senator. Public responses on social media showed a very positive perception of Komeng as having integrity, being trustworthy, humble, not arrogant, and actually getting down to work, not just attending formal meetings. The public also assessed that Komeng humor did not diminish his professionalism, but instead served as a bridge of humanistic communication between the people and state institutions. This study concluded that Komeng personal branding innovation after becoming a member of the DPD RI succeeded in creating an image of a public official who was credible, professional, popular, and relevant to the needs of the community.Komeng demonstrated that authenticity, integrity, and humanistic communication were able to increase public trust and strengthen the representative function of the DPD RI, while also becoming a new model of effective political communication in the digital era.